2013
DOI: 10.1136/annrheumdis-2013-203345
|View full text |Cite
|
Sign up to set email alerts
|

Sclerostin inhibition reverses systemic, periarticular and local bone loss in arthritis

Abstract: ObjectiveTo test whether inhibition of sclerostin by a targeted monoclonal antibody (Scl-Ab) protects from bone and cartilage damage in inflammatory arthritis. Sclerostin is a potent inhibitor of bone formation and may be responsible for the low level of bone repair in patients with rheumatoid arthritis.MethodsHuman tumour necrosis factor transgenic mice (hTNFtg mice) developing inflammatory arthritis and local and bone loss were administered either vehicle, anti-TNF antibody, Scl-Ab, or a combination of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 18 publications
1
56
2
Order By: Relevance
“…TNF-α transgenic mice are models of osteoporosis with dramatic decrease in bone mass and deterioration of bone microarchitecture. In addition, an over-expression of a Wnt inhibitor, sclerostin, has been observed in these models, with a consequence of inflammation-related decrease in bone formation (43). Moreover, alterations in other Wnt inhibitors, such as DKK1, might be involved in inflammation-related bone loss (44).…”
Section: N Discussion and Conclusionmentioning
confidence: 99%
“…TNF-α transgenic mice are models of osteoporosis with dramatic decrease in bone mass and deterioration of bone microarchitecture. In addition, an over-expression of a Wnt inhibitor, sclerostin, has been observed in these models, with a consequence of inflammation-related decrease in bone formation (43). Moreover, alterations in other Wnt inhibitors, such as DKK1, might be involved in inflammation-related bone loss (44).…”
Section: N Discussion and Conclusionmentioning
confidence: 99%
“…Therefore, sclerostin inhibition is considered as a potential, powerful tool to enhance bone repair in inflammatory arthritis. 47 In a research study on an experimental model in mice, Yao et al showed that treatment with monoclonal antibody against sclerostin (Scl-Ab) prevented glucocorticoid (GC)-induced reduction in both trabecular and cortical bone mass and strength, and appeared to maintain osteoblast activity through autophagy. 48 Glucocorticoids increase the expression of Wnt signaling antagonists (sclerostin and Dkk-1) in experimental studies on rodents.…”
Section: Inflammatory Diseases Related To Disorders Of Sclerostinmentioning
confidence: 99%
“…However, the role of sclerostin blockade in AS is not entirely clear, as patients with AS can also develop articular erosions. In arthritic hTNFtg mice, sclerostin blockade was shown to inhibit the local bone and cartilage damage that occurred in inflamed joints [133]. Therefore, sclerostin blockade may alleviate the bone erosions seen in erosive inflammatory arthritis.…”
Section: Mechanisms Of Bone Formation In Asmentioning
confidence: 99%